2017
DOI: 10.1038/ng.3921
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of neuroblastoma cell identity defined by transcriptional circuitries

Abstract: Neuroblastoma is a tumor of the peripheral sympathetic nervous system, derived from multipotent neural crest cells (NCCs). To define core regulatory circuitries (CRCs) controlling the gene expression program of neuroblastoma, we established and analyzed the neuroblastoma super-enhancer landscape. We discovered three types of identity in neuroblastoma cell lines: a sympathetic noradrenergic identity, defined by a CRC module including the PHOX2B, HAND2 and GATA3 transcription factors (TFs); an NCC-like identity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
605
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(647 citation statements)
references
References 43 publications
41
605
1
Order By: Relevance
“…We therefore profiled genome-wide distribution of H3K27Ac by ChIP-sequencing of JQ1 naive and resistant cells across both cell line models (Fig S3I-P). In concordance with previous studies, SE-associated genes: HAND1/2, GATA3, and PHOX2B , were identified in naive cells (Boeva et al, 2017; Chipumuro et al, 2014; van Groningen et al, 2017, Durbin et al, 2018). SE-marked genes and typical enhancer (TE)-marked genes, defined by high H3K27Ac signal in enhancer regions, were preferentially repressed by JQ1 (Figure S4A, B).…”
Section: Resultssupporting
confidence: 91%
“…We therefore profiled genome-wide distribution of H3K27Ac by ChIP-sequencing of JQ1 naive and resistant cells across both cell line models (Fig S3I-P). In concordance with previous studies, SE-associated genes: HAND1/2, GATA3, and PHOX2B , were identified in naive cells (Boeva et al, 2017; Chipumuro et al, 2014; van Groningen et al, 2017, Durbin et al, 2018). SE-marked genes and typical enhancer (TE)-marked genes, defined by high H3K27Ac signal in enhancer regions, were preferentially repressed by JQ1 (Figure S4A, B).…”
Section: Resultssupporting
confidence: 91%
“…Emerging data suggest that high‐risk neuroblastomas harbor a high degree of intratumor heterogeneity and contain tumor subclones with distinct genetic/epigenetic and/or phenotypic characteristics (Eleveld et al , ; Mengelbier et al , ; Schramm et al , ; Boeva et al , ; van Groningen et al , ; Braekeveldt et al , ; Karlsson et al , ). These findings suggest that general and/or combinatorial therapeutic strategies must be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of the three NB mRNAs correlated to each other, the combination of TH and PHOX2B mRNAs in BM increased the prognostic performance of either alone. This may be due to the limited number of study subjects or may reflect differences in the expression of TH and PHOX2B mRNAs in the neoplastic cells, which will require further studies in additional cohorts. In PB, PHOX2B mRNA significantly dichotomized the prognosis of the study cohort, identifying 23 (34%) patients with poor outcome (5‐year EFS = 29%, 95% CI: 12–48%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combination of high TH and PHOX2B mRNAs in BM for 23% of the study cohort was significantly associated with a poor outcome (5- Although the expression of the three NB mRNAs correlated to each other, the combination of TH and PHOX2B mRNAs in BM increased the prognostic performance of either alone. This may be due to the limited number of study subjects or may reflect differences in the expression of TH and PHOX2B mRNAs in the neoplastic cells, 21,22 which will require further studies in additional cohorts. In PB, PHOX2B 23 and advocating separate investigations of right and left BM aspirates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation